PENGEMBANGAN LEMBAR KERJA SISWA MENGGUNAKAN MODEL PROBLEM-BASED LEARNING BERBASIS BUDAYA LOKAL PADA SISWA KELAS XI SMA YPK MEDAN - Ramadhani, Rahmi (EDUTECH CONSULTANT, 2018)
This research was a research development with the reference Four-D model by Thiagarajan, Semmel and Semmel. Subject in this study were eleventh grade students in SMA YPK Medan. Student worksheets validation based on the opinion of the validator from lecturer and mathematics teacher. The practically of student worksheets was analyzed based on: (1) implementation of the used students worksheets in learning process; (2) student’s responses to worksheets developed; and (3) teacher’s responses to worksheets developed. The effectivenees of students worksheets was analyzed based on: (1) a minimum completeness mathematics student’s ability; (2) the ability of teachers to manage learning; and (3) student’s activity in learning process. The result showed that student worksheets used local-culture problem based learning in mathematics learning has been valid, practice and effective.